Unlocking Internet of Things (IoT) for Enhanced Knowledge Management and Organizational Performance: A Case Study of Diverse Industry Players in the Philippines - Sangalang, Raven Marie F.; Ancla, Lawrence Xavier C.; Chong, Miko Dominic L.; Wang, Jason Chester S.; Morales, Retchell Rubin L.; Caminong, Joliber M.; Tanpoco, Manuel R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Web 3.0 resulted in the increased decentralization of information, especially upon the emergence of the Internet of Things (IoT). IoT has revolutionized data transfer and has since reshaped knowledge management in organizations. This research focuses on how the IoT enables real-time data sharing and its impact on enhancing knowledge management and business processes in various local businesses. The study examines how five Philippine enterprises utilize the IoT through a qualitative embedded cross-case analysis. Several methods, like interviews, focus groups, and questionnaires, helped gather insights into how the IoT influences knowledge management processes. The research follows a case study approach, and the findings reveal that IoT boosts the generation, storage, sharing, and utilization of knowledge, aiding organizations in enhancing operational efficiency and product and service quality, thus improving business processes. Further, the research offers insights into the IoT possibilities. It provides practical recommendations for seamless integration through the companies' capabilities that enhance their knowledge management and operational results, gaining insights for strategic implementation.